Bridging the Gap in the Repair of Long-Gap Esophageal Atresia: Still Questions on Diagnostics and Treatment - von Allmen, Daniel; Wijnen, Rene M. H. (European Journal of Pediatric Surgery, 2015)
Long-gap esophageal atresia remains a complex surgical problem fraught with complications and poor outcomes in many patients. This review covers the techniques and strategies currently used to address this congenital anomaly. The techniques covered include preservation of the native esophagus, esophageal elongation techniques, esophageal replacement, and evolving work on tissue engineering.
Keywords: long-gap esophageal atresia; colon interposition; Foker technique